Simplify (2x– 3) (5×4 – 7×3 + 6×2 – 9) A. 10×5 – 29×4 + 33×3 – 18×2 18x + 27 B. 10×5 – x4-9×3 – 1

Question

Simplify

(2x– 3) (5×4 – 7×3 + 6×2 – 9)

A. 10×5 – 29×4 + 33×3 – 18×2 18x + 27
B. 10×5 – x4-9×3 – 18×2 -18x – 27
C. 10×5 + 29×4 – 33×3 + 18×2 + 18x – 27
D. 10×5 + x4 + 33×3 + 18×2 + 18x + 27

in progress 0
Thu Nguyệt 7 months 2021-07-21T01:58:02+00:00 1 Answers 2 views 0

Answers ( )

    0
    2021-07-21T01:59:33+00:00

    Answer: (A)=10×5−29×4+33×3−18×2−18x+27

    Step-by-step explanation:

    How i solved it was by simplifying each answer there was available and (A) was the most compatiable answer!

    =(2x+−3)(5×4+−7×3+6×2+−9)

    =(2x)(5×4)+(2x)(−7×3)+(2x)(6×2)+(2x)(−9)+(−3)(5×4)+(−3)(−7×3)+(−3)(6×2)+(−3)(−9)

    =10×5−14×4+12×3−18x−15×4+21×3−18×2+27

    =10×5−29×4+33×3−18×2−18x+27

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )